2005
DOI: 10.1097/01.bpo.0000150808.90052.7c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validation of the Multiplier Method for Predicting Limb Length Discrepancy and Outcome of Epiphysiodesis, Part II

Abstract: To validate the accuracy of the multiplier method in predicting limb length discrepancy (LLD) and outcome of epiphysiodesis, radiographs of 60 patients treated for LLD were measured. Data generated were used to predict maturity lengths of epiphysiodesed limbs, bone length discrepancies at maturity, and LLD at maturity after epiphysiodesis (residual discrepancy) using the multiplier and Moseley methods. The multiplier method mean error for bone length discrepancies predictions was 0.6 cm (SD = 0.6). Mean error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 15 publications
1
41
0
2
Order By: Relevance
“…The results of the present study are similar to that of Aguilar et al [1,2], who noted that the multiplier method erred as much as 4.4 cm when predicting adult heights for boys and 2.6-cm for girls 5-years-old and younger. Another study by Sanders et al [8] showed that use of the multiplier method can cause errors as great as 5 cm when used in patients who already had their growth spurt.…”
supporting
confidence: 81%
“…The results of the present study are similar to that of Aguilar et al [1,2], who noted that the multiplier method erred as much as 4.4 cm when predicting adult heights for boys and 2.6-cm for girls 5-years-old and younger. Another study by Sanders et al [8] showed that use of the multiplier method can cause errors as great as 5 cm when used in patients who already had their growth spurt.…”
supporting
confidence: 81%
“…В нашей работе мы использовали метод прогнозирования роста Multiplier, который лежит в основе работы компьютерного прило-жения для iPhone PaleyGrowth. Согласно данным D. Paley et al указанный метод достаточно точно определяет неравенство длин конечностей по до-стижении костной зрелости [32]. Величину пере-удлинения мы рассчитывали, исходя из насто-ящей длины сегмента и прогнозируемой длины здорового сегмента по достижении им костной зрелости.…”
Section: Discussionunclassified
“…Aguilar et al found that the Moseley method is as accurate as the multiplier method in predicting bone maturity lengths but less accurate in predicting limb length discrepancies at maturity after epiphyseodesis [26,27]. Dewaele and Fabry were not able to significantly improve their results in timing the skeletal age for epiphyseodesis by using the Moseley straight-line graph, and their principal source of error was in estimating the bone age [3].…”
Section: Discussionmentioning
confidence: 99%